Effect of preheating on the film thickness of contemporary composite restorative materials - Dimitrios Dionysopoulos; Kosmas Tolidis; Paris Gerasimou; Eugenia Koliniotou-Koumpia (Elsevier, 2014)
Background/purpose: Recently, the placement of composite materials at an elevated temperature has been proposed in order to increase their flow for better adaptation in cavity walls. The aim of this in vitro study was to evaluate the effect of preheating on the film thickness of a variety of commercially available conventional composites and to compare them with those obtained from a variety of flowable composites at room temperature. Materials and methods: The composites were three nanohybrid, two nanofilled, six microhybrid, one microfilled, one hybrid, and three packable composite resins, two compomers, four flowable composite resins and two flowable compomers. The conventional composite (0.05 mL) tested was placed between two matrix strip-covered glass plates and a load of 15 kg was applied vertically to the glass plates for a period of 180 seconds. The composite material was then light-cured and the thickness measured using a micrometer. Three measurements were made on each polymerized specimen and then averaged. The composite resins were placed into a commercially-available composite warmer, thermostatically controlled to 54°C or 60°C. Five specimens were made using each composite material at each temperature. Results: Heat reduced film thickness (P < 0.05). The thickness of films at room temperature and of preheated conventional composites was significantly greater than flowable materials (P < 0.05). There was no difference in thickness between composite resins preheated to 54°C and 60°C (P > 0.05). Conclusion: The film thickness of the composites tested is material dependent. The thickness of the preheated conventional composites is significantly lower than those at room temperature. The conventional composites provide film thickness values greater than those of the flowable composites regardless of preheating temperature.